1986
DOI: 10.1016/0022-474x(86)90012-3
|View full text |Cite
|
Sign up to set email alerts
|

Moisture sorption and the applicability of the Brunauer-Emmett-Teller equation for some dry food products

Abstract: Abstract-Moisture sorption studies have been carried out on 16 low moisture foodstuffs at 27°C and based on the major type of constituent, viz starch. fat, protein and high hygroscopicity. the isotherms have been divided into four groups. The moisture sorption behaviour over 0. 060.92 water activity of the foods has indicated that the Brunauer-Emmett-Teller (BET) equation is applicable generally up to 0.6 water activity. The storage stability aspects of foodstuffs with respect to water activity have been sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Differences between these values showed that blanching changed the capacity for binding water and also for availability of free water. The reported monolayer values for mushrooms were 3.4 -5.4 g/100 g solids [1,5,21]. Only the X m values obtained for the blanched samples seem to be in accordance with those reported in literature.…”
supporting
confidence: 91%
“…Differences between these values showed that blanching changed the capacity for binding water and also for availability of free water. The reported monolayer values for mushrooms were 3.4 -5.4 g/100 g solids [1,5,21]. Only the X m values obtained for the blanched samples seem to be in accordance with those reported in literature.…”
supporting
confidence: 91%
“…They were the data given by Abramovic and Klofutar (2006); Aviara et al (2004); Ayranci and Dalgis (1992); Brunauer et al (1940);Ditmar (1935); Geurts et al (1974); Iglesias and Chirife (1982); Iglesias et al (1997); Iguaz and Virseda (2007); Kargin (1957); KaymakErtekin and Gedik (2004); Kiranoudis et al (1993); Kumar and Balasubrahmanyam (1986); Labuza et al (1985); Lazarides (1991); Loncin et al (1968); Maroulis et al (1988); Peng et al (2007); Sitaula and Bhowmick (2006); Schär and Rüegg (1985); Timmermann and Chirife (1991); Trujillo et al (2003); Turhan and Gunasekaran (2002); van den Berg (1981); van den Berg (1984); van den Berg and Bruin (1981); Wolf et al (1972); Wolf et al (1984); Yamanaka et al (1989); Yanniotis and Zarmboutis (1996). The sorption isotherms were analysed on the basis of a w / wÀa w plots, using statgraphics applied to Eq.…”
Section: New Classification Applied To Selected Sorption Isothermsmentioning
confidence: 99%
“…Two equations are used to describe zone 1 and zone 2 of sorption isotherms, every one depend on the physical phenomenon associated. Guggenheim-Anderson-de Boer (GAB) refined the Langmuir and BET theories and proposed a new equation describes the full curve with three parameters having physical meanings [32,41].…”
Section: Adsorption/desorption Isotherms Fittingmentioning
confidence: 99%
“…Nevertheless, literature remains poor concerning technological properties such as shrinkage or swelling according to hygrometric variations [35][36][37]. This field of interest is widely treated in case of others hygroscopic materials such as wood [9,18,38], concrete [39,40], or agro alimentary materials [32,34,41,42].…”
Section: Introductionmentioning
confidence: 99%